Outdoor environments for physiotherapeutic rehabilitation of work-related stress : lying down in shelter, sitting in serenity, standing in nature and walking in coherence - Lundkvist, Peter (SLU/Dept. of People and Society, 2022)
Learning more about rehabilitating work-related stress is important since stress-related illness is creating a lot of human suffering and a significant economic loss in most countries. Physiotherapists are one of the most common professions in work-oriented rehabilitation in Sweden and previous research has shown positive results of using outdoor environments when rehabilitating work-related stress. Research has also displayed the preferred qualities of stressreducing and restorative outdoor environments, used in multi professional interventions. There is however no previous research found on displaying the specific environmental qualities which are beneficial in different types of physiotherapeutic exercises for rehabilitating work-related stress. In order to investigate the qualities of outdoor environments and how they are affecting physiotherapeutic exercises a qualitative study has been conducted, interviewing two physiotherapists who are currently working at two rehab gardens with rehabilitation of workrelated stress. The interviews have been thematically analysed and resulted in a display of the effect of the environmental qualities when doing physiotherapeutic exercises while: lying down, being seated, standing and walking; in the rehab garden, the nearby field, walk path and forest. The conclusion of this thesis is that the specific environmental qualities which are especially important in the different types of physiotherapeutic exercises are the sheltered quality while lying down, the serene quality while being seated, the natural quality while standing and the cohesive quality when conducting exercises while walking. There is a need for further research, evaluating the effect on the participants of the different environments used in physiotherapeutic exercises, in order to better support physiotherapists when using outdoor environments for rehabilitating workrelated stress.